The crystal structure of uranyl-oxide mineral schoepite, [(UO2)4O (OH)6]( H2O)6, revisited - Plasil,J. (Journal of Geosciences, 2018)
New single-crystal X-ray diffraction experiments have revealed that the crystal structure of schoepite, one of the more common U-oxide minerals, is centrosymmetric, rather than acentric as reported in the past. Schoepite is orthorhombic, space group Pbca, a = 16.7810(5), b = 14.7044(4), c = 14.2985(5) Å, with V = 3528.22(19) Å3 and Z = 8. Its structure was solved by charge-flipping algorithm and refined to an agreement index (R) of 4.7 % for 4662 unique reflections collected using microfocus X-ray source. Schoepite structure, in line with its previous determination, is based upon U-O-OH sheets of the fourmarierite topology and an interlayer filled only by molecular H2O. The complexity calculations show that the difference in complexity values between schoepite, [(UO2)4O(OH)6](H2O)6, and metaschoepite, [(UO2)4O(OH)6](H2O)5, are much smaller (about 100 bits/cell) then considered previously (about 1000 bits/cell). Such small difference is in line with the easy transformation of schoepite to metaschoepite under ambient conditions and a joint occurrence of both minerals.
Keywords: schoepite; uranyl-oxide mineral; crystal structure; centrosymmetric